First evidence of Retzius-sparing robot-assisted radical prostatectomy with the Versius robotic surgical system - Palagonia, Erika; Tappero, Stefano; Mazzone, Elio; Chierigo, Francesco; Buratto, Carlo; Caviglia, Alberto; Barbieri, Michele; Maltzman, Ofir; Cellini, Valerio; Napoli, Giancarlo; Olivero, Alberto; Strada, Elena; et al. (Frontiers in Oncology, 2025)
We describe the first experience of Retzius-sparing robot-assisted radical prostatectomy (RS-RARP) performed with the Versius robotic system (CMR Surgical, Cambridge, UK). Five patients underwent RS-RARP at ASST Grande Ospedale Metropolitano Niguarda (Milan, Italy) between May 2023 and December 2023. All procedures were completed with no complications or need for conversion. No arms collision or technical failure of the system was recorded. The median operative time was 244 minutes (interquartile range [IQR]: 190-300). Median length of stay was three days. Our initial experience suggests that RS-RARP with the Versius robotic system is a feasible procedure. This novel platform provides a flexible system environment that can be easily tailored to all types of surgery. However, some arrangements are still necessary, warranting future investigations in larger series.